Evaluation of suppliers in the tannery industry based on emergy accounting analysis: implications for resource conservation in emerging economies - Koppiahraj Karuppiah; Bathrinath Sankaranarayanan; Syed Mithun Ali (International Journal of Sustainable Engineering, 2022)
Emergy Accounting (EMA) has gained attention in recent times as an environmental accounting tool. So far, it has been used for analysis at national and regional levels; however, the EMA has not been utilised in a business performance analysis context. When used in a business context, EMA reveals the interface between industrial activity and the environment. EMA analysis can provide opportunities in measuring the social, economic, and environmental performance of the industry in a sustainability context. Unlike other evaluation methods, which are ‘demand-side’ or ‘user-side’ concerned, EMA analysis is a ‘donor-side’ approach. This research work illustrates the selection of suppliers based on the amount of emergy consumption. Emergy indicators, such as Emergy Yield Ratio (EYR), Emergy Sustainability Index (ESI), Environmental Loading Ratio (ELR), Emergy Self-support Ratio (ESR), Renewability percent (%R), Emergy flow Density (ED), and Emergy Investment Ratio (EIR) are estimated. The results show that there is enough room for improving emergy performance in the tannery industry. The result also highlights a significant variance in the input of indigenous renewable and non-renewable resources and imported resources among the investigated tanneries. Based on the outcomes, the study provides insights on the industries’ consumption of renewable and non-renewable resources.